Dunning-Kruger Effect dalam Aktivitas Dakwah di Media Sosial: Implikasi dan Upaya Pencegahannya - Ahmad Miftahun Ni'am; Muh Nur'Afwan (IAINU Kebumen, 2026)
The rapid development of social media has significantly transformed Islamic da'wah by enabling the dissemination of religious messages to reach broader audiences more efficiently. However, this accessibility has also given rise to challenges, particularly the emergence of the Dunning-Kruger Effect, a cognitive bias in which individuals with limited knowledge tend to overestimate their competence in conveying religious teachings. This study aims to examine the phenomenon of the Dunning-Kruger Effect in Islamic da'wah on social media, its impacts, and possible strategies to minimize its influence. This research employed a qualitative library research approach. The data were collected through an extensive review of books, scholarly journal articles, and previous studies related to the Dunning-Kruger Effect, Islamic da'wah, social media, and digital literacy. The data were analyzed using a descriptive-analytical method by identifying, examining, and synthesizing relevant concepts and research findings. The results indicate that the Dunning-Kruger Effect may contribute to the dissemination of inaccurate religious information, encourage unproductive debates in digital spaces, reduce public trust in qualified Islamic scholars and preachers, and foster a superficial understanding of religious knowledge. Therefore, strengthening religious competence, cultivating humility (tawadhu'), promoting tabayyun (information verification), upholding ethical principles in da'wah, encouraging continuous learning, and improving digital literacy are essential to ensuring that social media functions as a responsible, educational, and value-based platform for Islamic da'wah.